Effect of Different Estrus Synchronization Protocols on Some Reproductive Traits in Nubian Goats - Salim, Manal Abd El Wahid; Nikhaila , Abdel Moneim Mukhtar Abu; Adam, Ahmed Abdel Gadir; Eissa, Hussein Ibraheem Abu (University of Khartoum Journal of Agricultural Sciences, 2025)
The effect of estrus synchronization protocol on the conception rates and actual kidding percentage together with litter size, birth weight, twinning rates, sex of kids and sex ratio in Nubian goats were investigated. Eighteen Nubian goats were divided into three equal groups. The animals in group one were treated with vaginal sponges (VSP) impregnated with 45 mg flurogestone acetate (FGA) for 18 days, followed by a single dose of 400 i.u. of pregnant mare serum gonadotrophin (PMSG) upon removal of the VSP. The second group was subjected to a double injects of 7.5 mg prostaglandin (PGF2α), given eleven days apart. For the third group, a vasectomies buck was suddenly introduced and kept with the goats for 15 days to initiate estrus. Intact bucks were used to detect heat and mate with goats in the three groups. Does treated with PGF2α and those subjected to the buck effect showed significantly higher pregnancy rates (66.6%) than those treated with VSP+ PMSG. (33.3%). However, the protocols of synchronization had no effect on the kidding rates, litter size and birth weight. The type of birth comprised both singletons and twins, but none of the three groups